Experimental Evaluation of Herbivory on Live Plant Seedlings by the Earthworm Lumbricus terrestris L. in the Presence and Absence of Soil Surface Litter - Kirchberger, Johannes; Eisenhauer, Nico; Weisser, Wolfgang W.; Türke, Manfred (PLOS ONE, 2015)
Background Recent studies suggested that the earthworm Lumbricus terrestris might act as a seedling predator by ingesting emerging seedlings, and individuals were observed damaging fresh leaves of various plant species in the field. To evaluate the significance of herbivore behavior of L. terrestris for plant and earthworm performance we exposed 23- to 33-days-old seedlings of six plant species to earthworms in two microcosm experiments. Plants belonged to the three functional groups grasses, non-leguminous herbs, and legumes. Leaf damage, leaf mortality, the number of leaves as well as mortality and growth of seedlings were followed over a period of up to 26 days. In a subset of replicates 0.1 g of soil surface litter of each of the six plant species was provided and consumption was estimated regularly to determine potential feeding preferences of earthworms. Results There was no difference in seedling growth, the number of live seedlings and dead leaves between treatments with or without worms. Fresh leaves were damaged eight times during the experiment, most likely by L. terrestris, with two direct observations of earthworms tearing off leaf parts. Another nine leaves were partly pulled into earthworm burrows. Lumbricus terrestris preferred to consume legume litter over litter of the other plant functional groups. Earthworms that consumed litter lost less weight than individuals that were provided with soil and live plants only, indicating that live plants are not a suitable substitute for litter in earthworm nutrition. Conclusion Our results demonstrate that L. terrestris damages live plants; however, this behavior occurs only rarely. Pulling live plants into earthworm burrows might induce microbial decomposition of leaves to make them suitable for later consumption. Herbivory on plants beyond the initial seedling stage may only play a minor role in earthworm nutrition and has limited potential to influence plant growth.